MEAT SURFACE CONTAMINATION IN JIGJIGA: A MICROBIOLOGICAL STUDY OF ABATTOIRS AND RETAIL HOUSES - Abebe , G. Kebede; Anderson , James L. (Research Journal of Agriculture (RJA), 2024)
Slaughter facilities involved in various meat processing stages, such as skinning, evisceration, storage, and distribution, can serve as significant sources of contamination for meat and meat products. In developing countries, traditional methods of handling, processing, and marketing meat often undermine quality due to poor sanitation, leading to substantial product loss and increased risk of food-borne diseases. External contamination of meat, particularly in abattoirs, is a major concern, with microbial surface contamination of carcasses significantly impacting meat shelf life. Fecal matter is a primary source of microbial contamination, which can reach carcasses through direct deposition or indirect contact via contaminated equipment, surfaces, and workers. This study explores the extent of contamination in meat processing facilities in developing countries and highlights the critical need for improved sanitation practices to enhance meat quality and safety